Precursor B cell lymphoblastic lymphoma presenting as a solitary bone tumor: a case report and review of the literature - TOPTAŞ, TAYFUR (SPRINGER TOKYO, 2010)
Precursor B cell lymphoblastic lymphoma (B-LBL) is quite uncommon and it usually manifests as an extranodal disease. Although B-LBL may present with bone involvement, it is a very rare manifestation of B-LBL as a primary solitary bone tumor. Here, we report a case of precursor B-LBL presenting with solitary bone tumor and a review of a total of seven adult patients reported previously in the literature. We described demographic and clinical characteristics of these patients with unique presentation and discussed treatment options. Unlike previous reports except one case, our patient underwent allogeneic stem cell transplantation (allo-SCT) due to refractory disease. She is alive without evidence of disease by the post-transplant 12th month. B-LBL has an aggressive clinical course in adult patients and allo-SCT may be the best treatment option.
Keywords: Primary bone lymphoma; Precursor B cell lymphoblastic lymphoma; Solitary bone tumor; Allogeneic stem cell transplantation; INVOLVEMENT